(untitled) (Nigerian Journal of Technology, 2024)
The Full factorial and Box-Behnken Designs for determination of optimal values of wear rate using pin –on-disc wear test parameters have been successfully carried out. The parameters used are track diameter of the disc, mass difference of specimen before and after the test and speed of the disc. The mathematical model developed for the “smaller-the-better” wear rate response by the Full factorial and Box-Behnken Design methods were adjudged adequate with a p-value of 0.025 and 0.046 respectively. Also, the adjusted R2 values of the Factorial and Box-Behnken Designs were determined to be 0.89 and 0.69 respectively. The statistical ANOVA analysis carried out on the Box-Behnken Design showed that the track diameter and the mass difference were significant with a p-value of 0.041 and 0.007 respectively. Contour plots and response surface plot developed for the factorial method and the Box-Behnken Design displayed appreciable level of similarity. It was noticed that a reduction of wear was occasioned by an increase in track diameter and speed of the disc.